Literacy in Haryana - Decadal Change - 2001-2011: A Comparative Study of Literacy Rates in Different Districts of Haryana (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The present paper is an endeavor to ponder the proficiency rate in province of Haryana. For this reason, the paper considers the aggregate populace (by sex), sex proportion and education rates for areas of Haryana (by sex) according to registration 2001 and 2011. This paper reasons that education rate in Haryana expanded to 76.6 according to 2011 evaluation, out of which greatest proficiency rate has been found in the area of Gurgaon (84.4) and the most reduced in locale of Mewat (56.1). Male-female education rate gives a change hint. Sex proportion enhanced in every one of the regions of Haryana however observed to be greatest in the area of Mewat (906) and the most minimal sex proportion was found in the locale Gurgaon (853). The general sex proportion was expanded to 877 in the year 2011, which was 861 in the year 2001, yet at the same time it is at low level as contrast with national level of sex proportion that is 940 as per the enumeration 2011.